Tests for latent tuberculosis in candidates for solid organ transplantation: A systematic review and meta‐analysis. Issue 8 (6th July 2019) - Maung Myint, Thida; Rogerson, Thomas E.; Noble, Kristy; Craig, Jonathan C.; Webster, Angela C.
Abstract: Reactivation of latent tuberculosis following solid organ transplantation has serious consequences for the recipient. The most useful diagnostic test for latent TB is not clear. We conducted a systematic review and meta‐analysis to assess the relative test performance of interferon gamma release assays (IGRAs) and the tuberculin skin test (TST) in people undergoing solid organ transplantation. The clinical or radiological risk factors were used as the proxy reference standard. Test performance was expressed as an odd ratio (OR). We identified 24 studies (N = 7811), 12 studies compared IGRAs with TST directly, nine studies evaluated only TST and three studies only IGRAs. Direct comparison between tests and clinical risk factors indicated both tests were strongly associated with the presence of clinical risk factors for TB (TST: OR 3.17; 95%CI 1.55‐6.48, IGRA: OR 2.78; 95%CI 1.55‐5.01), and radiological evidence of past TB (TST: OR 3.26; 95%CI 1.85‐5.73, IGRA: OR 3.85; 95%CI 2.16‐6.86). Relative comparison indicated IGRAs positivity was more strongly associated with presence of radiological evidence of TB than TST (relative OR: 3.24; 95%CI 1.10‐9.56). While there is no strong evidence in supporting use of IGRAs over TST for diagnosing latent TB, IGRAs positivity is more associated with the presence of radiological evidence of previous TB.